Todo Corre, Mucho Fluye, Algo Permanece Cambio y Estabilidad Social - Montero, Maritza (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
A problem present in social sciences is addressed from a psychosocial perspective, showing how psychology has taken on some current ideas in their naturalized commonsensical version establishing that society is essentially dynamic, and that social changes simultaneously affect all social realms. In examining the scant responses given by social psychology, the disrupting effect of social change, or its individualistic realm is pointed out. A critical analysis of this situation is organized around several problematising questions: Why in spite of “revolutions” some things do not change? Why certain revolutionary achievements become “crystallized” (fixed)? How is it that in spite of authoritarianism and repressive actions changes are produced? This analysis focuses on the notions of habitus, and social reduction considering such aspects as psychological time, institutional time, and historical time, in order to construct an explanation of the processes leading to unfelt transformations, sorrowful changes, insufferable permanence, and comfortable upholdings.